Managing disasters: an imperative for development planning - Uprety, Singha Raj (1999)
In common parlance, disasters are understood as the human miseries caused by natural phenomena. But various sorts of disasters created by human misdeeds in the name of development are left almost oblivious and/or unfathomed. The major concern of this paper is centred around the `role of disaster management in managing development process'. This paper is divided into three sections. The first section deals with the background followed by the conceptual connotation of `disasters, disaster management and the causes of disasters' while planning developmental activities. The second section deals with the logical explanation about the relationship between development and disasters. This section further explains the concept of rational thinking about formulating a disaster-free planning process and the focus required for preparing non-disastrous plan in Nepal. And the third section attempts to outline the strategy and constraints pertaining to formulating and implementing disaster management based plan in Nepal. - Reproduced
Keywords: Development planning; Disaster management